Assessment of aerosol particles using a new index - Moghim Sanaz; Goftari Ehsan (E3S Web of Conferences, 2024)
Dry beds of lakes and surrounding areas play an important role in dust production. This work develops a new index called Aerosol Type Detection Index using the Extinction Coefficient and Depolarization Ratio. The developed index shows values between zero and 0.15 for desert dust and -0.3 to zero for polluted desert dust particles in two regions including the Aral Sea in Central Asia and Hamoun Lake in Sistan, Iran. Although the dried beds of these lakes are susceptible to strong winds, wind speed profiles show that north of the Aral Sea and northwest of Hamoun Lake can be dust storm sources in these regions.